The Effect of Tax Clearing Policy, Drive Thru Service System, and Tax Sanctions on Motor Vehicle Taxpayer Compliance - Ida Ayu Cahaya Dewanti; I Ketut Jati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of tax clearing policies, the Samsat Drive Thru service system, and tax sanctions on the compliance of Motor Vehicle Taxpayers at the Tabanan Samsat Joint Office. This research was conducted at the Tabanan Samsat Joint Office, the number of samples used was 100 taxpayers with the sampling technique of the accidental sampling method. The data collected was then analyzed using multiple linear regression analysis techniques. The results showed that the tax clearing policy, the Samsat Drive Thru service system, and tax sanctions had a positive effect on the compliance of the Motor Vehicle Taxpayer at the Tabanan Samsat Joint Office. The implication of this research is the need for intentions and external factors that cause taxpayers to be more obedient in paying Motor Vehicle Tax. In addition, the government's role in producing tax policies that can increase awareness of the importance of paying Motor Vehicle Tax.